An annotated checklist of Iranian Mesostigmata (Acari), excluding the family Phytoseiidae - Shahrooz Kazemi; Asma Rajaei (Persian Journal of Acarology)
The present checklist provides the results of a survey of collected and identified mesostigmatic mites in Iran (excluding the family Phytoseiidae) including 348 species belonging to 128 genera, 39 families, and 17 superfamilies of which one genus (Trachyuropoda Berlese, 1888) is a new record for Iranian mite fauna. It is annotated with some corrections to specific identities which have previously reported by Iranian literature and with known geographical and habitats distributions inIran. Suborders Sejida and Trigynaspida comprise three and seven recorded species belonging to two and six genera, respectively, and Monogynaspida (except the Phytoseiidae) with 338 species belonging to 120 genera. No species of the cohorts Heatherellina and Heterozerconina has been recorded fromIran yet.